Neurogranin Regulates Metaplasticity - Zhong, Ling; Gerges, Nashaat Z. (Frontiers in Molecular Neuroscience, 2020)
Long-term potentiation (LTP) and long-term depression (LTD) are two major forms of synaptic plasticity that are widely accepted as cellular mechanisms involved in learning and memory. Metaplasticity is a process whereby modifications in synaptic processes shift the threshold for subsequent plasticity. While metaplasticity has been functionally observed, its molecular basis is not well understood. Here, we report that neurogranin (Ng) regulates metaplasticity by shifting the threshold toward potentiation, i.e. increasing Ng in hippocampal neurons lowers the threshold for LTP and augments the threshold for LTD. We also show that Ng does not change the ultrastructural localization of CaMKII or calcineurin, critical enzymes for the induction of LTP and LTD, respectively. Interestingly, while CaMKII concentrates close to the plasma membrane, calcineurin concentrates away from the plasma membrane. These data, along with the previous observation showing Ng targets calmodulin (CaM) closer to the plasma membrane, suggest that shifting the localization of CaM within the dendritic spines and closer to the plasma membrane, where there is more CaMKII, may be favoring the activation of CaMKII versus that of calcineurin. Thus, the regulation of CaM localization/targeting within dendritic spines by Ng may provide a mechanistic basis for the regulation of metaplasticity.